The Three Rites of Hajj according to the Four Imāms - Wardat, Abdullah Munawar (Journal of Islamic and Religious Studies, 2021)
This research aims to explain the three rituals of Hajj, namely Al-Ifrad, Al-Tamattu’ and the Qeraan, and the legal rulings that entail from them. Based on that, this study has concluded that Hajj according to the four imams revolves around one meaning, which is the intention of the Sacred House of God in the face of veneration, and that the singular Hajj does not result in only one circumambulation, which is the Ifaadah circumambulation, and no blood is required on it, unlike the one who performs Hajj and the one who does it.